Synergistic Activity of Mixtures of Piper aduncum Fruit Extract and Three Microorganism-Derived Insecticides against the Diamond Back Moth, Plutella xylostella - Wanda Russianzi; Djoko Prijono (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2019)
Plutella xylostella is an important pest of Brassicaceae vegetable crops. Frequent use of insecticides containing single active ingredients can cause resistance in P. xylostella. This work was done to evaluate the synergism between Piper aduncum fruit extract and three microorganism-derived insecticides, i.e. abamectin, chlorfenapyr, and spinetoram, against P. xylostella from Pacet District, Cianjur Regency. Results of leaf-residue feeding bioassays with 48-h feeding treatment showed that LC95 of abamectin, chlorfenapyr, and spinetoram at 96 h after treatment (HAT) was about 5.8, 7.0, and 1.9-fold higher than their respective field rates. Thus, based on leaf-feeding assays P. xylostella larvae from Pacet-Cianjur were not susceptible to abamectin and chlorfenapyr, but were still fairly susceptible to spinetoram. LC95 of P. aduncum extract at 96 HAT was 0.68% (w/v). Based on combination index at the LC95 level - 96 HAT, mixtures of P. aduncum extract with all three test insecticides were synergistic. Thus, P. aduncum extract is potential to be used as an alternative ingredient to increase the effectiveness of the three test insecticides against P. xylostella.Keywords: Botanical insecticides, cabbage pest, insecticide mixtures, microorganism-derived insecticides, synergism.